Doping TiO2 with Cr and Cu Elements from Electroplating Wastewater as a Single Source for Improvement of the Photocatalyst Activity under Visible Light in the Degradation of Anionic Surfactant - Wahyuni, Endang Tri; Budi, Sulistyaning; Aurellia, Dea; Widianti, Rizky Aprilia; Lestari, Novianti Dwi; Jaafar, Nur Farhana; Suherman, Suherman (Indonesian Journal of Chemistry, 2024)
This paper discusses the use of electroplating wastewater containing Cr and Cu as a single dopant source to improve the activity of TiO2 photocatalysts under visible light. Sol-gel doping was used to dop TiO2 with Cr and Cu in the wastewater. The doped TiO2 photocatalysts were characterized using SRUV/visible and XRD instruments, and their effect on the degradation of linear alkyl benzene sulphonate (LAS) in laundry wastewater was evaluated. The electroplating wastewater used in this research contains Cr and Cu about 2000 and 20 mg/L, respectively. These metals were successfully doped into a TiO2 structure, which significantly reduced the gap energy of TiO2, allowing it to be more active under visible light. The highest photodegradation of the 125 mg/L LAS in 25 mL of the laundry wastewater with pH 7 was achieved by using 30 mg of TiO2/Cr-Cu (200/2) photocatalyst, which degraded up to 60% of LAS in 60 min. With the same conditions, the LAS photodegradation increased to 100% upon the second run. This approach can help turn hazardous electroplating wastewater into a valuable material to solve environmental problems.